Animal Identification and Records Monitoring Tool using RFID (AIRMTR) - Dipay, J M B; Fabregas, A C; Ado, R G (KnE Social Sciences, 2018)
This study was conducted to design, develop and initially implement the Animal Identification and Records Monitoring Tool using RFID. Specifically, it identified the problems encountered in conducting Manual Tagging for Animal Clinic; the appropriate features of the tool that can be developed to address the problems encountered, and the respondents’ level of acceptance of the user toward the developed tool in terms of functionality, reliability, usability, and performance. The research used the qualitative-quantitative research method that utilized a researcher-made questionnaire and interview questions. The respondents of the study were one (1) Animal Care Specialist representative, one (1) Pretty Paws representative, five (5) veterinarian representatives and eighty (80) pet owners from different places. The problems encountered in conducting tagging for animal clinic were traditional animal tag may cause death to some animals; animal diseases and injuries by animal tagging; duplication and confusion in using animal tagging; and difficulty in maintaining records of vaccination, medication health check-ups using animal tagging. The appropriate features of the tool that can be developed to address the problems encountered were: RFID can make the process of animal tagging faster and easier; and online scheduling and identification of pets in pet clinics are more convenient to use for both pet owners and veterinarians rather than the manual process. The respondents’ ratings for Animal Identification and Record Monitoring Tool using RFID were highly acceptable in terms of functionality (4.62); reliability (4.52); usability (4.68); and performance (4.59). The government agencies may suggest that animals should be tagged using the developed system for monitoring purposes. Further research on Internet controlled devices may be conducted other than stand-alone offline software programs. This study may also be developed considering the following features: UHF as a tracking device for animals; individual registered users to make page where the client can edit, rate and price; displaying hex value using LCD; access to the shop’s system to be validated; contraction number of the project with logo and clinic’s validation. Keywords: Animal Identification, Manual Tagging, RFID